Structure and function of intertracheary pits in hardwood - Sano, Y.(Hokkaido Univ., Sapporo (Japan)) (Mokuzai Gakkaishi, 2009)
Recent studies on the structure and function of intertracheary pits in hardwoods were reviewed. It is shown that the basic structure of intervessel pit membranes is more complicated than has been acknowledged previously. Physiological studies gave new insights into the regulation mechanisms of water flow by intervessel pit membranes. New findings are also reported regarding the fine structure of interfiber pit membranes and vessel to fiber pitting, and their association with water flow in xylem become a subject of tree physiological studies.